Anna Ishchuk. The Emergence of the First Women's Movements and Organizations in the United States of America - Ishchuk, Anna (Young Scholars Grinchenko – Seton International Journal, 2022)
The article provides a comprehensive analysis of the emergence of one of the central elements of US civil society – the women's movement and organizations. The author analyzed the main periods in the development of the women’s movement that are referred to by American researchers as waves. The review of the history of the women’s movement identified and characterized four waves of the women’s movement in the United States based on their goals, scale of activity, methods, and results of the struggle for gender equity in American society. The emergence of the women's movement is due to many reasons, including the development of society itself, at different historical stages, the women's movement took different forms. The evolution of women's movements in the United States shows the profound changes that have taken place in the behavior and consciousness of women over the centuries, we can trace a rather complex process of transforming women from political and social objects to very influential subjects. The subject of research is the main stages of development of the women's movement and organizations in the United States. The methodological bases of the study were general scientific research methods - systemic and structural-functional analysis. An important element was the historical-chronological method, which makes it possible to study the emergence, formation, and development of the women's movement in the United States, as well as to describe the main events in chronological order. By examining the emergence of the women's movement in the United States, through the characteristics of the main stages and features of its development, we understand that all changes in the status of American women, despite their objective inevitability, have occurred and continue to be realized as a result of concrete long and persistent work of the women's movement.